Genetic population structure and differentiation of Western Iranian Oxynoemacheilus argyrogramma (Heckel, 1847) using SSR markers - Kolangi-Miandare, Hamed (Mol Biol Res Commun, 2014)
This study was carried out to investigate the genetic diversity and population structure of 90 specimens of Oxynoemacheilus argyrogramma collected from Sepidbarg, Gamasiab and Ghaleji rivers, in the west of Iran. Analyses using three microsatellite loci indicated that the average number of alleles in the population was 12, which was well above the reported values for freshwater fishes. The expected (He) and observed (Ho) heterozygosity means were 0.865 and 0.576, respectively. Almost all loci showed deviation from the Hardy-Weinberg equilibrium (HWE). The results demonstrated that Oxynoemacheilus argyrogramma had desirable genetic diversity in the investigated regions.